Comparison of the efficacy and safety of hydroxyethyl starch 130/0.4 and Ringer's lactate in children with grade III dengue hemorrhagic fever - Risky Vitria Prasetyo; Abdul Latief Azis; Soegeng Soegijanto (Indonesian Pediatric Society Publishing House, 2009)
Background Theoretically hydroxyethyl starch (HES) will give more rapid recovery from shock, including in dengue shock syndrome (DSS) and currently gained popularity for its less deleterious effects on renal function and blood coagulation. Objectives To compare the efficacy and safety ofHES 130/0.4 and Ringer's lactate (RL) for shock recovery in children with DSS. Methods A randomized controlled study was performed on 39 children admitted with DSS at Dr. Soetomo Hospital, Surabaya, between March and May 2007. Children were grouped into grade III (n=25) and grade IV (n=14) dengue hemorrhagic fever (DHF) according to the WHO criteria. Within each group, subjects were randomly assigned to receive initial fluid resuscitation with either HES 130/0.4 (n=9 in the DHF grade III group, 10 in the DHF grade IV) or RL (n= 16 in the DHF grade III group, 4 in the DHF grade IV). Clinical and laboratory data were collected to determine improvements in shock recovery and adverse reactions. Results In both the grades III and IV DHF, HES 130/0.4 significantly decreased hemoglobin and hematocrit levels. Clinical improvements in pulse pressure and pulse rate were seen after treatment with HES 130/0.4 although these were statistically insignificant if compared to the RL group. No differences in fluid requirement and recurrent shock episodes were noted between the RL and HES groups. No adverse reactions were found during the study. Conclusion HES 130/0.4 administration is effective and safe in children with DSS.